Structural investigation of supply networks: A social network analysis approach - Kim, Yusoon; Choi, Thomas Y.; Yan, Tingting; Dooley, Kevin (Journal of Operations Management, 2011)
AbstractA system of interconnected buyers and suppliers is better modeled as a network than as a linear chain. In this paper we demonstrate how to use social network analysis to investigate the structural characteristics of supply networks. Our theoretical framework relates key social network analysis metrics to supply network constructs. We apply this framework to the three automotive supply networks reported inChoi and Hong (2002). Each of the supply networks is analyzed in terms of both materials flow and contractual relationships. We compare the social network analysis results with the case‐based interpretations inChoi and Hong (2002)and conclude that our framework can both supplement and complement case‐based analysis of supply networks.